Bright birds are cautious: seasonally conspicuous plumage prompts risk avoidance by male superb fairy-wrens. Issue 1857 (28th June 2017) - McQueen, Alexandra; Naimo, Annalise C.; Teunissen, Niki; Magrath, Robert D.; Delhey, Kaspar; Peters, Anne
Abstract : Increased predation risk is considered a cost of having conspicuous colours, affecting the anti-predator behaviour of colourful animals. However, this is difficult to test, as individual factors often covary with colour and behaviour. We used alarm call playback and behavioural observations to assess whether individual birds adjust their response to risk according to their plumage colour. Male superb fairy-wrens ( Malurus cyaneus ) change from a dull brown to conspicuous blue plumage each year, allowing the behaviour of different coloured birds to be compared while controlling for within-individual effects. Because the timing of colour change varies among males, blue and brown birds can also be compared at the same time of year, controlling for seasonal effects on behaviour. While blue, fairy-wrens fled more often in response to alarm calls, and took longer to emerge from cover. Blue fairy-wrens also spent more time foraging in cover and being vigilant. Group members appeared to benefit from the presence of blue males, as they reduced their response to alarms, and allocated less time to sentinel behaviour when a blue male was close by. We suggest that fairy-wrens perceive themselves to be at a higher risk of predation while in conspicuous plumage and adjust their behaviour accordingly.